COUNTERTRANSFERENCE: EXPLORING ETHICAL ISSUES AND THEIR IMPACT ON COUNSELING PRACTICE - Sabrina Tiara Putri Rahmani; Mutia Khaira (Study Program Guidance and Counseling, Univesitas Pendidik, 2024)
This research explores the ethical issues of countertransference in counseling, aiming to understand its impact on counseling services. Countertransference, the counselor's emotional response to the client, poses a nuanced set of ethical challenges in maintaining confidentiality, transparency, and cultural sensitivity. This study synthesizes existing literature to elucidate the conflicts emerging from countertransference management, addressing issues such as the counselor's emotional instability, issues of racism, or a decline in professionalism. Furthermore, the study suggests avenues for future research, emphasizing the need to investigate moderating factors like counselor experience, therapeutic approach, and client characteristics on countertransference impact. Incorporating diverse perspectives, including those of clients, is proposed to gain a more comprehensive understanding. Additionally, research interventions providing practical strategies for ethically managing countertransference could contribute to the development of contextually informed ethical guidelines for counseling practices. This research offers a foundation for refining ethical considerations in countertransference and enhancing the overall quality of psychoanalytic counseling services.